Finite element investigation of the incremental deformation of components - Sahari, Berkawi Bin (1984)
Many components in conventional and nuclear power plants and chemical plants are likely to be subjected to 'severe' loading conditions, i.e. loads which would cause cyclic plastic straining and/or incremental deformation (i.e. ratchetting). For operating temperatures above the creep threshold, creep strain also occurs, which may exacerbate the ratchetting of components. If ratchetting occurs, the components may fail either due to excessive deformation so that the components cannot function properly or due to incremental collapse.